Interdisciplinary Approach to Special Techniques - Undercover Investigations - Valeriu CUȘNIR; Andrei NASTAS (ACROSS)
Within the limits of the economic, social and legal dimensions of globalization, along with the social, economic, cultural and political benefits, there are also harmful phenomena such as social deviance and its many manifestations. In their wake, transnational and transcontinental organised crime, in its various forms, stands out: drug trafficking, illicit arms trafficking, trafficking in nuclear materials, terrorism, prostitution, paedophilia, money laundering, theft and smuggling of expensive cars, theft and smuggling of cultural heritage objects, kidnapping of businessmen and celebrities for the purpose of blackmail and extortion, corruption in multinational companies, perversion of government officials, truck and ship piracy, environmental pollution and theft of money through computers, etc. No less dangerous, with an increased degree of damage are manifestations of organized crime, property crime, tax evasion, corruption, crimes against the person, real estate, computer fraud, etc. committed on a national scale. Taken as a whole, transnational and national-level crimes affect public security, undermine the sovereignty of States and disrupt the proper functioning of economic, political and social institutions. For a proper perception and positioning of special (operative) investigative techniques, it is necessary to clarify the specific features of these categories of crimes, the manoeuvres of preparation and commission of these categories of crimes, the particularities of the material element, the characteristics of the active subjects, the consequences, the damage and other aspects.